FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR KUBIS DARI PROVINSI SUMATERA UTARA KE MALAYSIA - Juliana Br Simbolon; Jupianus Sitepu; Roida Ervina Sinaga (JURNAL AGROTEKNOSAINS, 2022)
During the current pandemic, the agricultural sector is a sector that is strong enough to face economic shocks and is still a mainstay in regional economic recovery The agricultural, forestry and right wing sector in 2020 continued to grow postively by 1,95 % when the economy contrasted by 1,07 % (BPS, 2021). The large contribution of the agricultural sector to the econmy of North Sumatera is also indicated by the role of the agricultural sector in employment.The aim of this study are : 1. Cabbage production has a positive and significant effect on the volume of cabbage export from North Sumatera Province to Malaysia.2. Malaysia’s real GDP has a positive and significant effect on the volume of cabbage exports from North Sumatera Province to Malaysia. 3. The rupiah exchange rate against the Malaysian ringgit has a negative and significant effect on the export volume of cabbage from the province of North Sumatera to Malaysia. 4. The export price of cabbage has a positive and significant effect on the volume of cabbage exports on the volume of cabbage exports from Indonesia.This research will be published in a nationally acrcredited journal : Quality University Agrotechnoscience journal.